2017
DOI: 10.1002/polb.24323
|View full text |Cite
|
Sign up to set email alerts
|

Photoresponsive and fluorescence behaviors of azobenzene‐containing amphiphilic block copolymers

Abstract: The effects of solvency and mole fraction of azobenzene moieties (f PAzoMA ) on the photoresponsive and fluorescence behaviors of poly(acrylic acid)-block-poly(6-[4-(4 0methoxyphenylazo)phenoxy]hexyl methacrylate) (PAA-PAzoMA) amphiphilic diblock copolymers were investigated using UV-vis spectroscopy and fluorescence spectroscopy. The photoresponsive behavior depended strongly on the solvency and f PAzoMA . When dissolved in a PAA-selective solvent, PAA-PAzoMA formed micelles with PAzoMA in the micelle core. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…Such behavior indicated that the confined domains generated by the self-assembly of Azo and PEG facilitated the organization of azobenzene molecules. Studies have suggested that when azobenzene molecules are confined, such as in azobenzene-containing homopolymers, in microphase-separated domains of block copolymers, or in the core of micelles, mesogens tend to assemble into H-aggregation [23,25,26,46]. Although the self-assembly of azobenzene molecules and PEG through hydrogen bonds was unable to form compact microdomains to heavily turn nonassociated mesogens into aggregated mesogens, as micelles and block copolymers do, the formation of Azo/PEG complexes could nonetheless facilitate the aggregation of mesogens.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such behavior indicated that the confined domains generated by the self-assembly of Azo and PEG facilitated the organization of azobenzene molecules. Studies have suggested that when azobenzene molecules are confined, such as in azobenzene-containing homopolymers, in microphase-separated domains of block copolymers, or in the core of micelles, mesogens tend to assemble into H-aggregation [23,25,26,46]. Although the self-assembly of azobenzene molecules and PEG through hydrogen bonds was unable to form compact microdomains to heavily turn nonassociated mesogens into aggregated mesogens, as micelles and block copolymers do, the formation of Azo/PEG complexes could nonetheless facilitate the aggregation of mesogens.…”
Section: Resultsmentioning
confidence: 99%
“…Synthetic methods for preparing azobenzene-containing polymers with well-defined photochemical and photochemical properties have been reported extensively [16,18,19,20,21,22,23,24,25,26]. Although these approaches provide precise control of theses polymers′ molecular structures, the multistep synthetic routes are costly in terms of both time and money.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize that the mechanism that underlies the effect concerns photochemical cis ‐ trans isomerization of the dye molecules. A similar effect has been observed to date with various compounds that belong to the same group of azobenzene derivatives as the EB dye that we used . These results substantiate our hypothesis and provide a focus for the further investigation of the effect background.…”
Section: Resultsmentioning
confidence: 99%
“…We estimated the lifetime of the “tagged” molecules to be approximately 1 second, which corresponds to the data published in the literature . Although the effect of the light‐driven fluorescent enhancement was discussed in the literature, no data were published with respect to the EB complexes.…”
Section: Introductionmentioning
confidence: 99%
“…The fluorescence enhancement of azobenzene derivatives can be induced by trans to cis photoisomerization of azobenzene under UV light irradiation, aggregation-induced emission (AIE), and the fluorescence resonance energy transfer (FRET) process, according to the literature. [56][57][58][59][60] Herein, fluorene-azo oligomers in chloroform were exposed to 365 nm light to investigate their fluorescence changes. 4F in chloroform was also irradiated under the same conditions for comparison.…”
Section: Changes In Fluorescent Emission Induced By Photoisomerizationmentioning
confidence: 99%